Folate-Targeted mRNA Delivery Using Chitosan-Functionalized Selenium Nanoparticles: Potential in Cancer Immunotherapy - Fiona Maiyo; Moganavelli Singh (MDPI AG, 2019)
Systemic messenger RNA (mRNA) delivery, although still in its infancy, holds immense potential for application in cancer vaccination and immunotherapy. Its advantages over DNA transfection make it attractive in applications where transient expression is desired. However, this has proved challenging due to mRNA’s instability and susceptibility to degradation. Selenium is important for immune function and modulation, with selenium nanoparticles (SeNPs) finding a niche in biomedicine as drug delivery vehicles, owing to their biocompatibility, low toxicity, and biodegradability. In this investigation, we synthesized chitosan-coated SeNPs with a folic acid targeting moiety for Fluc mRNA delivery to cancer cells in vitro. Synthesized SeNPs were stable and well dispersed, and ranged from 59 to 102 nm in size. Nanoparticles bound and protected mRNA from RNase degradation, while exhibiting low cytotoxicity in the human embryonic kidney (HEK293), breast adenocarcinoma (MCF-7), and nasopharyngeal (KB) cells in culture. Moderate cytotoxicity evidenced in the colorectal carcinoma (Caco-2) and colon carcinoma (HT-29) cells was attributed to apoptosis induction by selenium, as confirmed by acridine orange/ethidium bromide staining. Selenium uptake studies corroborated the transfection results, where significant transgene expression was evident for the overexpressed folate receptor-positive KB cells when compared to the other cells with less or no folate receptors.